2015
DOI: 10.1136/emermed-2015-205217
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta (REBOA): a population based gap analysis of trauma patients in England and Wales

Abstract: IntroductionNon-compressible torso haemorrhage (NCTH) carries a high mortality in trauma as many patients exsanguinate prior to definitive haemorrhage control. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an adjunct that has the potential to bridge patients to definitive haemostasis. However, the proportion of trauma patients in whom REBOA may be utilised is unknown.MethodsWe conducted a population based analysis of 2012–2013 Trauma Audit and Research Network (TARN) data. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 27 publications
3
36
1
1
Order By: Relevance
“…Utilising the inclusion criteria proposed in this study, 3.2% of patients would have been eligible to undergo REBOA, similar to that reported by Barnard et al 4 (5.4%). Among the inclusion criteria proposed is the prior administration of high dose amine.…”
Section: Discussionsupporting
confidence: 84%
“…Utilising the inclusion criteria proposed in this study, 3.2% of patients would have been eligible to undergo REBOA, similar to that reported by Barnard et al 4 (5.4%). Among the inclusion criteria proposed is the prior administration of high dose amine.…”
Section: Discussionsupporting
confidence: 84%
“…REBOA has recently found use as a general technique across major emergency centers in Japan. The highest density of potential REBOA patients is also seen at major trauma centers in England and Wales, although the number of patients in whom REBOA was utilized is small [9]. In fact, a review of the potential use of REBOA in exsanguinating hemorrhage cases in the US suggested that this new technique should be thoroughly evaluated for broad use, but the literature currently suffers from a dearth of human studies on REBOA [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although we controlled for this in our study, the differences between REBOA and ACC in general need more context for accurate interpretation. In Japan, ACC currently seems to be a preferred intervention tactic in non-survivable injury cases and this differs from other countries, possibly making Japanese ACC-related mortality rates non-indicative of actual outcomes [1, 9, 13]. In addition, other patient characteristics such as better Glasgow Coma Scale (GCS) scores in cases where REBOA was used versus ACC cases (with more severe GCS scores) may also skew results.…”
Section: Discussionmentioning
confidence: 99%
“…Partial inflation with controlled hypotensive target allowed benefits overcome risks of a defective procedure. REBOA adoption, even in a potentially dangerous position, gave authors time to move patient from OR to angiographic room (not available at the moment in our hospital a hybrid surgical angiographic suite) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and time to find the primary source in a severe and multiple hemorrhagic trauma, with good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%